Quartz sand proppant for fracturing and preparation method thereof

By preparing a modified epoxy resin coating agent and quartz sand, the problem of poor flow diversion ability of existing quartz sand proppants is solved, and the quartz sand proppants with high spherical, low density and high flow diversion ability are achieved, which meets the Fracturing construction requirements.

CN119490841AInactive Publication Date: 2025-02-21SICHUAN GUANGKUANG NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411584185.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing quartz sand proppants have poor flow diversion capabilities after crushing, making it difficult to meet the needs of high spherical, low volume density, low crushing rate and high flow diversion capabilities.

Method used

The first generation polymer was prepared by the preparation of modified epoxy resin coating agents, including ulotropine and tromethamine reaction, and the yellow transparent viscous polymer was prepared by ring-opening reaction with bisphenol A epoxy resin, and finally The hydroxy-terminated polydimethylsiloxane is grafted onto a yellow transparent viscous polymer to obtain a modified epoxy resin coating agent, and a quartz sand proppant for fracturing is prepared in combination with quartz sand.

Benefits of technology

The prepared quartz sand proppant has high spherical, low density and high flow diversion capabilities, which significantly improves the flow diversion capabilities after crushing and meets the needs of fracturing construction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005123899260000021
    Figure BDA0005123899260000021
  • Figure BDA0005123899260000022
    Figure BDA0005123899260000022
  • Figure BDA0005123899260000031
    Figure BDA0005123899260000031
Patent Text Reader

Abstract

The invention discloses a quartz sand proppant for fracturing and a preparation method thereof, and relates to the technical field of quartz sand proppants. The proppant comprises the following raw materials in parts by weight: 25-50 parts of quartz sand and 5 parts of a modified epoxy resin coating agent. A first-generation polymer is prepared through the reaction of urotropine and tromethamine, then the first-generation polymer reacts with maleic anhydride to prepare a white crystalline solid, and then the white crystalline solid and bisphenol A epoxy resin are subjected to a ring-opening reaction to prepare a yellow transparent viscous polymer. And finally, grafting hydroxyl-terminated polydimethylsiloxane to the yellow transparent viscous polymer to obtain a modified epoxy resin film coating agent, and then mixing the modified epoxy resin film coating agent with quartz sand to obtain the quartz sand proppant for fracturing. The quartz sand proppant for fracturing prepared by the invention has high sphericity, low density and high flow conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of quartz sand proppants, and in particular to a quartz sand proppant for fracturing and a preparation method thereof. Background Art

[0002] In recent years, with the rapid development of the world economy and the rapid progress of science and technology, the demand for oil and natural gas remains high. Hydraulic fracturing technology is an important means to increase the production of oil and gas wells. It has been widely used in the development of various oil and gas wells. In the process of hydraulic fracturing, the role of proppant is crucial. Proppant is a key material for fracturing construction of low permeability oil and gas wells and shale gas reservoirs. It is a product with high added value. Its performance determines the success or failure of hydraulic fracturing technology and also affects the service life of oil and gas wells. Quartz sand is a natural mineral with high hardness, good stability and wide distribution. It is mainly produced in river beaches, deserts or coastal areas. Quartz sand is abundant in resources, cheap, low in density, and easy to pump with fracturing fluid, but its compressive strength is low, and its conductivity is greatly reduced after crushing. Therefore, it is particularly important to develop a proppant with high sphericity, low bulk density, low crushing rate and high conductivity.

[0003] The Chinese invention patent with publication number CN115851254A discloses a double-phobic modified quartz sand proppant and a preparation method thereof. The proppant is modified from quartz sand and nanoemulsion. The modification of the proppant includes the following steps: using styrene, fluoroacrylate, methacryloyloxyethyl trimethyl ammonium chloride, and diethylene glycol divinyl ether as functional monomers, preparing the nanoemulsion by soap-free emulsion polymerization; then adding quartz sand to the nanoemulsion for stirring reaction modification, filtering, and drying to obtain the double-phobic quartz sand proppant. The quartz sand proppant prepared by the invention is simple to prepare, hydrophobic and oleophobic, but its fragmentation rate and conductivity are poor. Summary of the invention

[0004] In view of the shortcomings of the prior art, the object of the present invention is to provide a quartz sand proppant for fracturing and a preparation method thereof.

[0005] To achieve the above object, the present invention is implemented through the following technical solutions:

[0006] A quartz sand proppant for fracturing, comprising the following raw materials in parts by weight: 25-50 parts of quartz sand and 5 parts of modified epoxy resin coating agent.

[0007] The modified epoxy resin coating agent is prepared by the following method:

[0008] S1: Deionized water, hexamethylenetetramine, tromethamine, and glacial acetic acid are added to the reactor in sequence, stirred and dissolved, heated to 65-75°C, reacted for 1-2 hours, cooled to room temperature and separated, the water layer was removed, and washed with deionized water for 3 times to obtain a first-generation polymer. The reaction equation is shown as follows:

[0009]

[0010] S2: Acetone, maleic anhydride, first-generation polymer, and sodium acetate are added to the reactor in sequence, stirred and dissolved, and the temperature is raised to reflux for reaction for 2-4 hours. Recrystallization is performed three times with acetone to obtain a white crystalline solid. The reaction equation is shown as follows:

[0011]

[0012] S3: Add acetone, white crystalline solid and bisphenol A epoxy resin to the reactor in sequence, stir and dissolve, raise the temperature to 30-50°C, react for 4-6 hours, and distill under reduced pressure to obtain a yellow transparent viscous polymer. The reaction equation is as follows:

[0013]

[0014] S4: Under nitrogen protection, DMF, yellow transparent viscous polymer, and hydroxyl-terminated polydimethylsiloxane are added to the reactor, stirred and dissolved, and the temperature is raised to 50-60°C, and then 85wt% phosphoric acid is added, reacted for 2-4h, and post-treated to obtain a modified epoxy resin coating agent. The reaction equation is shown as follows:

[0015]

[0016] Among them, m and n are natural numbers, and —M— represents:

[0017]

[0018] In the step S1, the mass ratio of deionized water, hexamethylenetetramine, tromethamine and glacial acetic acid is 10:2.5:(1.0-1.2):(0.8-1.0).

[0019] In the step S2, the feed mass ratio of acetone, maleic anhydride, first-generation polymer and sodium acetate is 50:(6-8):(18-20):(0.6-1).

[0020] In the step S3, the mass ratio of acetone, white crystalline solid and bisphenol A epoxy resin is 30:(8-10):(10-12).

[0021] In the step S4, the feed mass ratio of DMF, yellow transparent viscous polymer, hydroxyl-terminated polydimethylsiloxane, and 85 wt % phosphoric acid is (20-30):(8-10):(2-6):(0.1-0.3).

[0022] A method for preparing a quartz sand proppant for fracturing, characterized in that it comprises the following steps:

[0023] S1: Weigh quartz sand by weight, wash it 3 times with deionized water, wash it once with anhydrous ethanol, and wash it once with petroleum ether, and dry it in an electric heated blast drying oven at 80-100° C. for 4-6 hours to obtain a precursor;

[0024] S2: Mixing the modified epoxy resin coating agent and DMF at room temperature to obtain a viscous modified epoxy resin coating agent;

[0025] S3: Add the precursor and the viscous modified epoxy resin coating agent into the reactor, stir at 100-120° C. for 4-6 hours, and then dry at 105-115° C. for 10-12 hours to obtain quartz sand proppant for fracturing.

[0026] Due to the adoption of the above technical solution, the beneficial effects of the present invention include:

[0027] (1) The present invention prepares a first-generation polymer by reacting urotropine and tromethamine, and then reacts the first-generation polymer with maleic anhydride to prepare a white crystalline solid, and then reacts with bisphenol A epoxy resin through a ring-opening reaction to prepare a yellow transparent viscous polymer, and finally grafts hydroxyl-terminated polydimethylsiloxane to the yellow transparent viscous polymer to obtain a modified epoxy resin coating agent, which is then mixed with quartz sand to obtain a quartz sand proppant for fracturing. The prepared proppant has high sphericity, low density and high conductivity.

[0028] (2) The modified epoxy resin coating agent prepared by the present invention contains a large number of oxidized functional groups, wherein the epoxy and hydroxyl groups in the epoxy resin give the resin high reactivity, so that the cured resin has strong cohesion and adhesion, and the benzene ring gives the polymer heat resistance and rigidity. On the other hand, the epoxy and hydroxyl groups also react with the silanol groups in the organosilicon to embed the -Si-O- chain segments into the main chain of the epoxy resin, thereby increasing the compatibility of the system and making the prepared proppant have low density, high mechanical strength and good flow conductivity. DETAILED DESCRIPTION

[0029] The invention will be further described below in conjunction with the embodiments, but the invention is not limited to these embodiments.

[0030] Example 1

[0031] Preparation of modified epoxy resin coating agent:

[0032] S1: 100 g of deionized water, 25 g of urotropine, 10 g of tromethamine, and 8 g of glacial acetic acid were added to the reactor in sequence, stirred and dissolved, heated to 65°C, reacted for 2 h, cooled to room temperature, separated, the water layer was removed, and washed with deionized water for 3 times (100 g of deionized water each time) to obtain a first-generation polymer;

[0033] S2: 500 g acetone, 60 g maleic anhydride, 180 g first-generation polymer, and 6 g sodium acetate were added to the reactor in sequence, stirred to dissolve, heated to reflux for 2 h, and recrystallized with acetone three times (100 g acetone each time) to obtain a white crystalline solid;

[0034] S3: 300 g of acetone, 80 g of white crystalline solid and 100 g of bisphenol A epoxy resin (E51) were added to the reactor in sequence, stirred and dissolved, heated to 30°C, reacted for 6 h, and distilled under reduced pressure at 40°C for 5 h to obtain a yellow transparent viscous polymer;

[0035] S4: Under nitrogen protection, 200g DMF, 80g yellow transparent viscous polymer, and 20g hydroxyl-terminated polydimethylsiloxane (JZH-203) were added into the reactor, stirred to dissolve, heated to 50°C, and then 1g 85wt% phosphoric acid was added. The reaction was continued for 4h, and rotary evaporated at 40°C. The mixture was recrystallized three times with acetone (150g acetone was used each time), and vacuum dried at 60°C for 8h to obtain a modified epoxy resin coating agent.

[0036] Example 2

[0037] Preparation of modified epoxy resin coating agent:

[0038] S1: 100 g of deionized water, 25 g of urotropine, 11 g of tromethamine, and 9 g of glacial acetic acid were added to the reactor in sequence, stirred and dissolved, heated to 70°C, reacted for 1.5 h, cooled to room temperature to separate layers, removed the water layer, and washed with deionized water for 3 times (100 g of deionized water each time) to obtain a first-generation polymer;

[0039] S2: 500 g acetone, 70 g maleic anhydride, 190 g first-generation polymer, and 8 g sodium acetate were added to the reactor in sequence, stirred to dissolve, heated to reflux for 3 h, and recrystallized with acetone three times (100 g acetone each time) to obtain a white crystalline solid;

[0040] S3: 300 g of acetone, 90 g of white crystalline solid and 110 g of bisphenol A epoxy resin (E51) were added to the reactor in sequence, stirred and dissolved, heated to 40°C, reacted for 5 h, and distilled at 50°C under reduced pressure for 4 h to obtain a yellow transparent viscous polymer;

[0041] S4: Under nitrogen protection, 250g DMF, 90g yellow transparent viscous polymer, and 40g hydroxyl-terminated polydimethylsiloxane (JZH-203) were added into the reactor, stirred to dissolve, heated to 55°C, and then 2g 85wt% phosphoric acid was added. The reaction was continued for 3h, and rotary evaporated at 50°C. The mixture was recrystallized with acetone three times (150g acetone was used each time), and vacuum dried at 70°C for 6h to obtain a modified epoxy resin coating agent.

[0042] Example 3

[0043] Preparation of modified epoxy resin coating agent:

[0044] S1: 100 g of deionized water, 25 g of urotropine, 12 g of tromethamine, and 10 g of glacial acetic acid were added to the reactor in sequence, stirred and dissolved, heated to 75°C, reacted for 1 h, cooled to room temperature to separate layers, removed the water layer, and washed with deionized water for 3 times (100 g of deionized water each time) to obtain a first-generation polymer;

[0045] S2: 500 g acetone, 80 g maleic anhydride, 200 g first-generation polymer, and 10 g sodium acetate were added to the reactor in sequence, stirred and dissolved, heated to reflux for 4 h, and recrystallized with acetone three times (100 g acetone each time) to obtain a white crystalline solid;

[0046] S3: 300 g of acetone, 100 g of white crystalline solid and 120 g of bisphenol A epoxy resin (E51) were added to the reactor in sequence, stirred and dissolved, heated to 50° C., reacted for 4 h, and distilled at 60° C. under reduced pressure for 3 h to obtain a yellow transparent viscous polymer;

[0047] S4: Under nitrogen protection, 300g DMF, 100g yellow transparent viscous polymer, and 60g hydroxyl-terminated polydimethylsiloxane (JZH-203) were added into the reactor, stirred to dissolve, heated to 60°C, and then 3g 85wt% phosphoric acid was added, reacted for 2h, rotary evaporated at 60°C, and then recrystallized three times with acetone (using 150g acetone each time), and vacuum dried at 80°C for 4h to obtain a modified epoxy resin coating agent.

[0048] Example 4

[0049] Preparation of quartz sand proppant for fracturing:

[0050] S1: Weigh 2.5 kg of quartz sand, wash it 3 times with deionized water (1 kg of deionized water is used each time), wash it once with 1.5 kg of anhydrous ethanol, and then wash it once with 2 kg of petroleum ether, and dry it in an electric blast drying oven at 80 ° C for 6 h to obtain a precursor;

[0051] S2: 500 g of modified epoxy resin coating agent (prepared in Example 1) and 1 kg of DMF were mixed at room temperature to obtain a viscous modified epoxy resin coating agent;

[0052] S3: 2.5 kg of the precursor and 500 g of a viscous modified epoxy resin coating agent were added into a reactor, stirred at 100° C. for 6 h, and then dried at 105° C. for 12 h to obtain a quartz sand proppant for fracturing.

[0053] Example 5

[0054] Preparation of quartz sand proppant for fracturing:

[0055] S1: Weigh 3.75 kg of quartz sand, wash it with deionized water for 3 times (1 kg of deionized water is used each time), wash it with 1.5 kg of anhydrous ethanol once, and then wash it with 2 kg of petroleum ether once, and dry it in an electric blast drying oven at 90 ° C for 5 h to obtain a precursor;

[0056] S2: 500 g of modified epoxy resin coating agent (prepared in Example 2) and 1 kg of DMF were mixed at room temperature to obtain a viscous modified epoxy resin coating agent;

[0057] S3: 3.75 kg of the precursor and 500 g of a viscous modified epoxy resin coating agent were added into a reactor, stirred at 110° C. for 5 h, and then dried at 110° C. for 11 h to obtain a quartz sand proppant for fracturing.

[0058] Example 6

[0059] Preparation of quartz sand proppant for fracturing:

[0060] S1: Weigh 5.0 kg of quartz sand, wash it 3 times with deionized water (1 kg of deionized water each time), wash it once with 1.5 kg of anhydrous ethanol, and then wash it once with 2 kg of petroleum ether, and dry it in an electric blast drying oven at 100 ° C for 4 h to obtain a precursor;

[0061] S2: 500 g of modified epoxy resin coating agent (prepared in Example 3) and 1 kg of DMF were mixed at room temperature to obtain a viscous modified epoxy resin coating agent;

[0062] S3: 5.0 kg of the precursor and 500 g of a viscous modified epoxy resin coating agent were added into a reactor, stirred at 120° C. for 4 h, and then dried at 115° C. for 10 h to obtain a quartz sand proppant for fracturing.

[0063] Comparative Example 1

[0064] The preparation method of quartz sand proppant for fracturing is as follows: weigh 2.75 kg of quartz sand, wash it 3 times with deionized water (using 1 kg of deionized water each time), wash it once with 1.5 kg of anhydrous ethanol, and then wash it once with 2 kg of petroleum ether, and dry it in an electric blast drying oven at 90° C. for 5 hours to obtain quartz sand fracturing proppant.

[0065] Comparative Example 2

[0066] The preparation method of the quartz sand proppant for fracturing is basically the same as that of Example 5, except that step S2 is prepared by the following method:

[0067] 88 g of hydroxyl-terminated polydimethylsiloxane (JZH-203), 187 g of white crystalline solid (prepared in step S2 of Example 2), 225 g of bisphenol A epoxy resin (E51) and 1 kg of DMF were mixed at room temperature to obtain a viscous coating agent.

[0068] Comparative Example 3

[0069] The preparation method of quartz sand proppant for fracturing is basically the same as that of Example 5, except that the modified epoxy resin coating agent (prepared in Example 2) in step S2 is replaced by an equal weight of the membrane material prepared in step (1) of Example 3 in Publication No. CN117625171A.

[0070] Comparative Example 4

[0071] The amphiphobic modified quartz sand proppant B was prepared using the raw material composition and process in Example 2 of the Chinese invention patent specification with publication number CN115851254A.

[0072] The epoxy resin used in the examples and comparative examples of the present application is of model E51, purchased from Hunan Baling Petrochemical Company; the quartz sand specification is 140 mesh, purchased from Inner Mongolia Changfan Quartz Sand Co., Ltd.; the hydroxyl-terminated polydimethylsiloxane is of brand JZH-203, purchased from Yunnan Zhonghe Silicon-based New Materials Co., Ltd.

[0073] The quartz sand proppants for fracturing prepared in Examples 4-6 of the present application and Comparative Examples 1-4 were tested for sphericity, bulk density, apparent density and crushing rate. The test results are shown in Table 1.

[0074] The sphericity, bulk density, and crushing rate of the proppant are measured and calculated with reference to SY / T5108-2014 "Test Method for Proppant Performance for Hydraulic Fracturing and Gravel Packing Operations", and the conductivity is measured and calculated with reference to SY / T6302-2019 "Test Method for Conductivity of Fracturing Proppants".

[0075] Table 1

[0076]

[0077] It can be seen from Table 1 that the quartz sand proppants for fracturing prepared in Examples 4-6 of the present application have excellent sphericity, bulk density, crushing rate and conductivity.

[0078] Comparative Example 1 is a comparative example of a quartz sand proppant for fracturing prepared without adding a modified epoxy resin coating agent. From the data in Table 1, it can be seen that the crushing rate is 4.56% at 69 MPa and the conductivity is 26.12 μm. 2 ·cm.

[0079] The modified epoxy resin coating agent added in Comparative Example 2 is a viscous coating agent obtained by mixing 88g of hydroxyl-terminated polydimethylsiloxane (JZH-203), 187g of white crystalline solid (prepared in step S2 of Example 2), 225g of bisphenol A epoxy resin (E51) and 1kg of DMF at room temperature. As can be seen from Table 1, the crushing rate is 4.08% at 69MPa and the flow conductivity is 28.54μm 2 ·cm.

[0080] The modified epoxy resin coating agent added in Comparative Example 3 is the membrane material prepared in step (1) of Example 3 in Publication No. CN117625171A. As can be seen from Table 1, its breakage rate is 2.31% at 69 MPa and its flow conductivity is 35.43 μm. 2 ·cm.

[0081] Comparative Example 4 is a amphiphobic modified quartz sand proppant made by the raw material composition and process in Table 2 of the Chinese invention patent specification of CN115851254A. As can be seen from Table 1, its crushing rate is 3.12% at 69MPa and its conductivity is 27.23μm. 2 ·cm.

[0082] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. However, any equivalent changes, modifications and evolutions made by ordinary technicians in the field without departing from the scope of the technical solution of the present invention by using the technical content disclosed above are all equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.

Claims

1. A quartz sand proppant for fracturing, characterized in that: The proppant comprises the following raw materials in parts by weight: 25-50 parts of quartz sand and 5 parts of modified epoxy resin coating agent; The modified epoxy resin coating agent is prepared by the following method: S1: Deionized water, hexamethylenetetramine, tromethamine, and glacial acetic acid are added to the reactor in sequence, stirred and dissolved, heated to 65-75°C, reacted for 1-2h, cooled to room temperature, separated, the water layer was removed, and washed with deionized water for 3 times to obtain a first-generation polymer; S2: Add acetone, maleic anhydride, first-generation polymer, and sodium acetate into the reactor in sequence, stir and dissolve, heat to reflux for 2-4 hours, and recrystallize three times with acetone to obtain a white crystalline solid; S3: Add acetone, white crystalline solid and bisphenol A epoxy resin into the reactor in sequence, stir and dissolve, raise the temperature to 30-50°C, react for 4-6h, and distill under reduced pressure to obtain a yellow transparent viscous polymer; S4: Under nitrogen protection, DMF, yellow transparent viscous polymer, and hydroxyl-terminated polydimethylsiloxane are added into the reactor, stirred and dissolved, heated to 50-60° C., and then 85 wt % phosphoric acid is added, reacted for 2-4 hours, and post-treated to obtain a modified epoxy resin coating agent.

2. The quartz sand proppant for fracturing according to claim 1, characterized in that: In the step S1, the mass ratio of deionized water, hexamethylenetetramine, tromethamine and glacial acetic acid is 10:2.5:(1.0-1.2):(0.8-1.0).

3. The quartz sand proppant for fracturing according to claim 1, characterized in that: In the step S2, the feed mass ratio of acetone, maleic anhydride, first-generation polymer and sodium acetate is 50:(6-8):(18-20):(0.6-1).

4. The quartz sand proppant for fracturing according to claim 1, characterized in that: In the step S3, the mass ratio of acetone, white crystalline solid and bisphenol A epoxy resin is 30:(8-10):(10-12).

5. The quartz sand proppant for fracturing according to claim 1, characterized in that: In the step S4, the feed mass ratio of DMF, yellow transparent viscous polymer, hydroxyl-terminated polydimethylsiloxane, and 85 wt % phosphoric acid is (20-30):(8-10):(2-6):(0.1-0.3).

6. A method for preparing the quartz sand proppant for fracturing according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1: Weigh quartz sand by weight, wash it 3 times with deionized water, wash it once with anhydrous ethanol, and wash it once with petroleum ether, and dry it in an electric blast drying oven at 80-100° C. for 4-6 hours to obtain a precursor; S2: Mixing the modified epoxy resin coating agent and DMF at room temperature to obtain a viscous modified epoxy resin coating agent; S3: Add the precursor and the viscous modified epoxy resin coating agent into the reactor, stir at 100-120° C. for 4-6 hours, and then dry at 105-115° C. for 10-12 hours to obtain quartz sand proppant for fracturing.

Citation Information

Patent Citations

  • Amphiphobic and oleophobic modified quartz sand proppant and preparation method thereof

    CN115851254A

  • Quartz sand proppant for fracturing and preparation method thereof

    CN117625171A